KONSEP KESETARAAN GENDER DALAM PEMBANGUNAN DAN PEMBERDAYAAN EKONOMI MASYARAKAT - Afni, Nur; Rezal, Mohammad; Latoki, Labandingi (Musawa: Journal for Gender Studies, 2022)
One of the important elements in human development is economic growth that is equitably distributed between generations, between ethnicities, between genders, and between regions. One of the dimensions emphasized is the existence of gender equality. This dimension is also one of the development commitments and gender inequality that occurs in various parts of the world. Development in principle must provide justice and prosperity to all people, to men and women, to the rich and the poor. The current fact is that development has sharpened the gap in social justice between the poor and the rich, between women and men, between the ruling group and the common people. This can be seen from the existence of gender inequality in development.